Expression of Disappointment Emotions in 1-3 Year Old Children in Psycholinguistic Studies - Hasibuan, Mutiara Sany; Harahap, Rosmawaty (International Journal of Multidisciplinary Approach Research and Science, 2024)
This study uses a psycholinguistic approach to examine how children aged between one and three years old show disappointment. The study aims to find, examine and characterize the words or phrases used by children to express disappointment. The approach used is a descriptive qualitative analysis based on phonological and syntactic theories of child language acquisition. Naturally, conversational data were collected by documenting the events that made children feel disappointed. The findings of the analysis showed that children often used nonverbal cues such as roaring, shouting, and crying along with explanations to convey their dissatisfaction. Children aged 1 year and 4 months have only learned verbs and nouns at the syntactic level. Two-year-olds can say two words classified as verbs, nouns, pronomina and negative phrases. Children between two and nine years old can say two nouns, verbs, adjectives, or adverbs.